Pengaruh Intensitas Komunikasi Interpersonal dalam Grup WhatsApp Keluarga terhadap Tingkat Kepercayaan Diri Mahasiswa - Ana Tri Lestari; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to examine the influence of interpersonal communication intensity within family WhatsApp groups on university students’ self-confidence levels. The research is motivated by the shift in family communication patterns in the digital era, where WhatsApp serves as a primary medium for exchanging information, providing emotional support, and maintaining daily interaction. A quantitative survey method was employed, involving 100 students who met the criteria of being members of a family WhatsApp group for at least six months and actively engaging in communication. The research instrument measured two variables—interpersonal communication intensity and student self-confidence—both of which were tested for validity and reliability. The results of the regression analysis indicate that interpersonal communication within family WhatsApp groups has a positive and significant effect on students’ self-confidence. Higher levels of communication frequency, responsive interaction, and emotional closeness within the group contribute to increased student self-confidence. These findings affirm that digital family communication continues to play an essential role in supporting students’ psychological development.